1994
DOI: 10.3758/bf03213979
|View full text |Cite
|
Sign up to set email alerts
|

Temporal discounting and preference reversals in choice between delayed outcomes

Abstract: Subjects chose between pairs of hypothetical amounts of money available after different delays. When smaller, more immediate amounts were selected over larger, more delayed amounts, the addition of a constant delay to both outcomes resulted in reversals of preference, contrary to the standard discounted utility model of economics. The delays at which preference reversed were determined for three pairs of amounts ($20 vs. $50, $100 vs. $250, and $500 vs. $1,250). The relation between the delay to the larger amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
275
3
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(300 citation statements)
references
References 16 publications
17
275
3
5
Order By: Relevance
“…This definition has led to the development of a quantitative model referred to as delay discounting (Mazur, 1987) that suggests that the value of a reinforcer is discounted or devalued as a result of its delay to presentation. This model has been supported by the findings from numerous experiments (e.g., Green et al, 1994;Madden et al, 1997;Mazur, 1987Mazur, , 1998Myerson and Green, 1995;Petry and Casarella, 1999). (1999) showed that substance abusers discounted delayed outcomes at greater rates than non-abusers.…”
Section: Introductionmentioning
confidence: 70%
“…This definition has led to the development of a quantitative model referred to as delay discounting (Mazur, 1987) that suggests that the value of a reinforcer is discounted or devalued as a result of its delay to presentation. This model has been supported by the findings from numerous experiments (e.g., Green et al, 1994;Madden et al, 1997;Mazur, 1987Mazur, , 1998Myerson and Green, 1995;Petry and Casarella, 1999). (1999) showed that substance abusers discounted delayed outcomes at greater rates than non-abusers.…”
Section: Introductionmentioning
confidence: 70%
“…Preference reversals were also observed in humans by Green, Fristoe, and Myerson (1994), who used a procedure analogous to that used in the pigeon study but with hypothetical monetary rewards. In one condition, for example, people were asked whether they would prefer $20 now (smaller, sooner) or $50 in 1 year (larger, later).…”
Section: Discounting and Choice Between Delayed Rewardsmentioning
confidence: 83%
“…According to hyperbolic discounting, the discount rate associated with a fixedtime interval (e.g., a fixed delay to receive money) is not constant as required by compound discounting, but declines as the interval becomes more remote. This leads to dynamically inconsistent choices (Thaler 1981, Ainslie and Haendel 1983, Green et al 1994, in which an individual does not choose according to plans that were optimal from an earlier vantage point. For example, someone who chooses to receive two apples in eight days over one apple in a week is likely to reverse that preference one week later, choosing one apple immediately over two the next day.…”
Section: Introductionmentioning
confidence: 99%
“…First, there is an old concern, voiced in moralistic writing as well as in economics, that humans are myopic and do not value the future enough (e.g., see discussions of this perspective by Ainslie 2001, Loewenstein 1992. Second, there is a more recent concern, grounded in experimental evidence, that the value or utility of future events is discounted according to a hyperbolic, rather than compound, function (Rachlin et al 1991, Ainslie and Haslam 1992, Green et al 1994, Kirby and Marakovic 1995. According to hyperbolic discounting, the discount rate associated with a fixedtime interval (e.g., a fixed delay to receive money) is not constant as required by compound discounting, but declines as the interval becomes more remote.…”
Section: Introductionmentioning
confidence: 99%